Sun and rain : exploring seasons in Hawaiʻi - Feeney, Stephanie (University of Hawaiʻi Press, 2008)
Throughout the year there are changes in the weather called seasons. Many parts of the world have four seasons: winter, spring, summer, and fall. In Hawaiʻi we have two: the dry, sunny season and the wet, rainy season.